Match-Fixing and Betting Fraud in Football Law - Ünver, Yener (Sports and Law: Finding a Balance Between the Game and the Rules, 2026)
The manipulation of sporting events, illegal betting activities, and the granting of unfair advantages through conduct that violates the rules of sport fall within the scope of criminal law. The central issues of sports law extend beyond doping and acts of violence to include the manipulation of sporting events, bribery of athletes, coaches, or referees, illegal betting, and participation in or facilitation of such activities. These offenses undermine not only the integrity of sport but also public confidence in sporting competitions and therefore have significant societal implications. The legal consequences of such conduct are not confined to private law. It is not merely a question of spectators being deprived of their legitimate expectation of a fair and unpredictable sporting contest despite having purchased admission. Rather, criminal law serves a broader public function by safeguarding the integrity of sport, protecting the public interest, and preserving individuals' opportunities for self-realization and personal development through fair sporting competition and entertainment. In recent years, the increasing use of information and communication technologies to facilitate match manipulation and illegal betting has contributed to a substantial rise in transnational criminal activity in this field. The considerable illicit profits generated by these offenses often fuel other forms of organized crime, including money laundering, corruption, tax evasion, and, in some cases, the financing of terrorist activities.